Lactobacillus gasseri PA-3, but not L. gasseri OLL2996, reduces the absorption of purine nucleosides in rats. (3rd June 2018) - Kano, H.; Yamada, N.; Saito, C.; Murayama-Chiba, Y.; Asami, Y.; Ito, H.
ABSTRACT: Lactobacillus gasseri PA-3 (PA-3) is a bacterial strain with a strong ability to degrade purine nucleosides. We previously showed that PA-3 incorporates purines in vitro and that oral administration of PA-3 and purines to rats attenuated their absorption of purines. It remains unclear whether these effects of PA-3 depend on bacterial strains. This study therefore compared the abilities of PA-3 and another bacterial strain of L. gasseri, OLL2996, which has shown decreased ability to degrade purine nucleosides in vitro, to incorporate purine nucleosides and to inhibit the absorption of purines fed to rats. Each bacterial strain was incubated in the presence of 14 C-adenosine or 14 C-inosine and the incorporation of each purine was evaluated by measuring their radioactivity. In vivo, rats were fed 14 C-labeled purines along with PA-3 or OLL2996 and the absorption of these 14 C-labeled purines was evaluated by analyzing radioactivity of blood samples. PA-3 incorporated about twice as much 14 C-adenosine and 14 C-inosine as OLL2996. The elevation of radioactivity levels in blood was 10–20% lower in rats treated with PA-3 than in control rats, after feeding with both 14 C-adenosine and 14 C-inosine as purines. In contrast, treatment with OLL2996 did not have statistically significant effects on radioactivity compared with the control group. These results indicate that the magnitude of bacterial inhibition of purine absorption is dependent on bacterial strain, correlating at least partly with the ability to incorporate and degrade purines.